Digital Safety for Moms: Cyber ​​Security and Digital Security Education: Socialization for PKK Mothers in Kertamukti Village - Deni Sopiyan; Reza Hana Utama; Arnie Gusmiarni; Siska Sri Wahyuni; Usan Sulasmi; Asti Setiawati; Aliva Amalianty; Sandi Sukmana; Muhammad Rizki Ramadhan; Annisa Nurul Fajri; Siti Nurlatifah (LPPM STMIK Mardira Indonesia, 2025)
The community service team of academics and students from STMIK Mardira Indonesia has executed a community service initiative focused on digital safety concerns for the PKK moms in Kertamukti Village, Cipatat District. This initiative aims to educate the PKK moms in Kertamukti Village. The swift progression of digital technology has simplified daily tasks for homemakers. Nonetheless, these conveniences entail possible digital security threats, including online fraud, personal data theft, and malware proliferation stemming from a lack of awareness of safe technology usage. This community service initiative aims to enhance digital literacy and raise awareness of cybersecurity among PKK mothers in Kertamukti Village, with a specific focus on recognizing digital scam tactics, creating secure passwords, and implementing preventive measures against cyberattacks. This activity employs interactive presentations, actual case simulations, and direct coaching via conversations and interviews regarding the safe use of digital applications. The outcomes of this initiative are anticipated to enhance mothers' understanding and competencies in safeguarding personal data, as well as to cultivate a positive digital culture within their households.